Risk of Subsequent Bone Cancers Among 69 460 Five-Year Survivors of Childhood and Adolescent Cancer in Europe. (26th September 2017) - Fidler, Miranda M.; Reulen, Raoul C.; Winter, David L.; Allodji, Rodrigue S.; Bagnasco, Francesca; Bárdi, Edit; Bautz, Andrea; Bright, Chloe J.; Byrne, Julianne; Feijen, Elizabeth A. M.; Garwicz, Stanislaw; Grabow, Desiree; et al.
Abstract: Introduction: We investigate the risks of subsequent primary bone cancers after childhood and adolescent cancer in 12 European countries. For the first time, we satisfactorily address the risks beyond 40 years from diagnosis and beyond 40 years of age among all survivors. Methods: This largest-ever assembled cohort comprises 69 460 five-year survivors of cancer diagnosed before age 20 years. Standardized incidence ratios, absolute excess risks, and multivariable-adjusted relative risks and relative excess risks were calculated. All statistical tests were two-sided. Results: Overall, survivors were 21.65 times (95% confidence interval = 18.97 to 24.60 times) more likely to be diagnosed with a subsequent primary bone cancer than expected from the general population. The greatest excess numbers of bone cancers were observed after retinoblastoma, bone sarcoma, and soft tissue sarcoma. The excess number of bone cancers declined linearly with both years since diagnosis and attained age (all P < .05). Beyond 40 years from diagnosis and age 40 years, there were at most 0.45 excess bone cancers among all survivors per 10 000 person-years at risk; beyond 30 years from diagnosis and age 30 years, there were at most 5.02 excess bone cancers after each of retinoblastoma, bone sarcoma, and soft tissue sarcoma, per 10 000 person-years at risk. Conclusions: For all survivors combined and the cancer groups with the greatest excess number of bone cancers, the excess numbers observed declined with both age and years from diagnosis. These results provide novel, reliable, and unbiased information about risks and risk factors among long-term survivors of childhood and adolescent cancer.